Exponential Attractor for a Class of Nonclassical Diusion Equation (Journal of Partial Differential Equations, 2020)
In this paper, we consider the asymptotic behavior of solutions for a class of nonclassical diffusion equation. We show the squeezing property and the existence of exponential attractor for this equation. We also make the estimates on its fractal dimension and exponential attraction.